The Influence of Ground Water Level Conditions on the Stability of Road Slopes with Retaining Walls - Priadi, Eka; Murad, Murad (Universitas Negeri Padang, 2023)
This research was carried out using the P laxis 8.0 finite element method and manual calculations as well as by evaluating the safety factor value. Slope stability analysis using the P laxis program aims to determine the safe value of the slope before and after reinforcement using a cantilever - type retaining wall. Based on the analysis of the P laxis program before the installation of the cantilever retaining wall, in general the condition of the retaining wall on Jalan Ahmad Yani Gg. Batu Mas, Singkawang City experienced a landslide due to the condition of the soil which was classified as having low soil mechanical properties. Slopes with designed cantilever wall reinforcement are considered safer because they have the smallest displacement and settlement values, and meet all slope stability requirements, ie, shear stability is 1.251 > 1.5 (Safe), stability against overturning is 2.415 > 2 (Safe) , and bearing capacity is 0.555 < 0.583. The cantilever retaining wall structure uses D16-100 principal reinforcement and D10-100 shrinkage reinforcement, the base plate uses D16-150 principal reinforcement and D10-100 shrinkage reinforcement.